Pamidronate Attenuates Oxidative Stress and Energetic Metabolism Changes but Worsens Functional Outcomes in Acute Doxorubicin-Induced Cardiotoxicity in Rats - Carvalho, Paula Bernardo De [UNESP]; Gonçalves, Andréa De Freitas [UNESP]; Alegre, Patrícia Helena Correa [UNESP]; Azevedo, Paula Schmidt [UNESP]; Roscani, Meliza Goi [UNESP]; Bergamasco, Carolina Marabesi [UNESP]; Modesto, Pamela N. [UNESP]; Fernandes, Ana Angélica [UNESP]; Minicucci, Marcos Ferreira [UNESP]; Paiva, Sergio Alberto Rupp [UNESP]; Antonio, Leonardo [UNESP]; Zornoff, Mamede [UNESP]; et al. (Karger Publishers, 2016)
Background: Cardiotoxicity is the major side effect of doxorubicin. As mechanisms that are involved in cardiotoxicity are ambiguous, new methods for attenuating cardiotoxicity are needed. Recent studies have shown that bisphosphonates can decrease oxidative stress. Therefore, the objective of this study was to evaluate the effect of pamidronate on preventing acute doxorubicin-induced cardiotoxicity. Methods: Sixty-four male Wistar rats were allocated into four groups: the control group (C), the pamidronate group (P), the doxorubicin group (D) and the doxorubicin/pamidronate group (DP). The rats in the P and DP groups received pamidronate injections (3 mg/kg, IP). After 24 hours, the rats in the D and DP groups received doxorubicin injections (20 mg/kg, IP). Forty-eight hours after doxorubicin injection, the rats were killed. Echocardiography, isolated heart study and biochemical analysis were performed. Results: Doxorubicin-induced acute cardiotoxicity showed increased matrix metalloproteinases (MMP)-2 activation, oxidative damage and induced alterations in myocardial energetic metabolism. Pamidronate did not inhibit MMP-2 activation but attenuated oxidative stress and improved myocardial energetic metabolism. Regarding cardiac function, the DP group exhibited a decrease in the left ventricular ejection fraction in the echocardiography and a decrease in +dP/dt in the isolated heart study compared with other groups. The same DP group presented serum hypocalcaemia. Conclusions: Despite its ability to reduce oxidative stress and improve energy metabolism in the heart, pamidronate worsened systolic function in rats treated with doxorubicin, and therefore we cannot recommend its use in conjunction with anthracycline chemotherapy.
Keywords: Hypocalcaemia; Isolated heart study; Left ventricular dysfunction; Matrix metalloproteinase